Optimal duration of antimicrobial prophylaxis in patients undergoing distal pancreatectomy: A multicenter cohort study - Kenjiro Okada; Kenichiro Uemura; Sohei Satoi; Tsutomu Fujii; Manabu Kawai; So Yamaki; Toru Watanabe; Hideki Motobayashi; Shinya Takahashi (Annals of Gastroenterological Surgery)
Abstract Background Antimicrobial prophylaxis is routinely administered in patients undergoing distal pancreatectomy, with cephalosporins being the most frequently used agents. However, there is limited evidence regarding optimal duration of antimicrobial prophylaxis. This study aimed to evaluate the optimal duration of antimicrobial prophylaxis in distal pancreatectomy. Methods A multicenter cohort study was performed using a common database of patients who underwent distal pancreatectomy between April 2017 and March 2022 at four high‐volume centers in Japan. Eligible patients were divided into two groups according to the duration of antimicrobial prophylaxis: intraoperative or up to 24 h after surgery and more than 24 h after surgery. Primary endpoint was the incidence of surgical site infections. Results A total of 496 patients were enrolled in this study, including 254 and 242 patients categorized into the intraoperative or up to 24‐h and more than 24‐h groups, respectively. Surgical site infections occurred in 129 patients (26%). The intraoperative or up to 24‐h group had a significantly lower incidence of surgical site infection (19% vs. 33%, p < 0.001) and infectious clinically relevant postoperative pancreatic fistula (8% vs. 17%, p = 0.002). There were no significant differences in severe surgical site infection rates between the groups. Multivariate logistic regression identified more than 24‐h administration of antimicrobial prophylaxis as an independent risk factor for surgical site infections (p = 0.001). Conclusion Prolonged administration of antimicrobial prophylaxis may not be effective in preventing surgical site infections after distal pancreatectomy compared to intraoperative or up to 24‐h administration.